Kemampuan Pemecahan Masalah Dalam Fisika Dengan Pembelajaran Generatif Berbantuan Scaffolding Dan Advance Organizer - Prelia Dwi Amanah; Ahmad Harjono; I Wayan Gunada (Department of Physics Education, Universitas Mataram, 2017)
Generative learning has an advantage in the process of receiving new knowledge, so that learners need a medium in understanding a phenomenon that occurs. This research can help in dealing with the problem of scaffolding and advance organizers. The population in this study is all students of class XI SMA Negeri 4 Mataram academic year 2016/2017. Sampling was done by purposive sampling technique, and this quasi experimental study used non-equivalent group design design with pre-test and post test. The results obtained from the class given generative treatment scaffolding assisted and advanced organizer have the same increase. In both classes expected the same as the previous ability, but the difference between the two is not much different. Therefore, there is no effect of generative learning model with scaffolding and advance organizer on ability.